Theatre and medicine - Garner, Stanton B., 1955- (Theatre&., 2023)
"Theatre and Medicine offers a tour of this interdisciplinary terrain. Organized into four distinct topics, each represents crucial ways of understanding the theatre-medicine relationship. From discussions on the somatic underpinnings of the body that medicine and theatre take as their subject through to the historical association of theatre and contagion, and the pervasive role of doctors and the practitioners of alternative medicine in Western theatre and role of patients on and off stage. Together, this brief study considers the institutional contexts of theatre's medical performances in the early twenty-first century"--